TEOLOGI BENCANA DALAM AL-QUR'AN - Affandi, Abdullah (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2020)
Seeing the reality that has occurred lately, where disasters have befallen mankind, especially CoVid-19, many experts have then sought justification at the theological level. The role of God is a constant debate. There are those who think that the disasters that occur are a form of God's wrath for human behavior, others think that the disasters that occur are a form of testing from God to the servants they love. This article will try to briefly review how the Koran talks about what happens to humans (disasters or calamities) and how the theology of disasters is formulated in the Qur'an.Keywords: theology, Qur’an, balaa, fitnah